EVALUATION AND FOLLOW-UP STUDY OF A SUMMER SCIENCE AND MATHEMATICS PROGRAM FOR TALENTED SECONDARY SCHOOL STUDENTS. - Cooley, William W.; Bassett, Robert D. (Science Education, 1961)
The article evaluates the summer science and mathematics institutes for talented high school students in the U.S. In an attempt to inquire into the consequences of the program, an independent study was undertaken at the Harvard Graduate School of Education to evaluate and follow-up one of the summer institutes Thayer Academy in Braintree, Massachusetts. A primary conclusion of the investigation is that standardized instruments are finally becoming available for science education research which can detect changes in student behavior in areas other than mastery of the facts and principles of science and can detect changes over relatively short periods of time. Details of the objectives and procedures of the study are presented in this article.